Re-Union : How Bold Labor Reforms Can Repair, Revitalize, and Reunite the United States - Madland, David (Book collections on Project MUSE., 2021)
"The central argument of this book is that stronger unions operating under a new type of labor system could help address America's underlying economic and political challenges. The new system would be built around two central ideas: active policy support for unions and broad-based collective bargaining"--